A Pragmatic Analysis of Expressive Speech Acts in Online Comments on Nightbirde’s Audition - Mulyadi Mulyadi; Afriana Afriana (LPPM Universitas Bumigora Mataram, 2026)
Expressive acts are a major category within illocutionary speech acts. This research aimed to explore and classify expressive speech acts in YouTube comments reacting to Nightbirde’s audition on America’s Got Talent. The analysis is grounded in the expressive speech act theory proposed by Searle and Vanderveken (2009). This research employs a qualitative descriptive method to analyze the data. Data were collected through non-participatory observation and note-taking. From 38 individual comments, 60 data points were identified. The analysis revealed four expressive speech act types: compliment (25 times), thank (13 times), condole (14 times), and lament (8 times). Other types, such as apologize, boast, congratulate, protest, complain, greet, welcome, and deplore, did not appear in the dataset. These results suggest that digital platforms like YouTube foster emotionally expressive discourse, especially in moments of shared mourning. The researcher encourages further exploration of expressive speech acts in varied online contexts, including multimodal forms such as emojis, visuals, and interactional features.